Aggressive angiomyxoma: The first case report in skull - Cao, Zexin; Miao, Lifeng; Liu, Min; Liu, Wenyu; Zhang, Hengrui; Liu, Xuchen; Wang, Jiwei; Wang, Xinyu (Frontiers in Surgery, 2022)
Aggressive angiomyxoma (AAM) is a rare mesenchymal tumor primarily growing in the soft tissue of the pelvis and perineum in women of reproductive age. It is a benign tumor that still has a probability of being accompanied by localized invasion. Although negative margins of resection are difficult to achieve due to the invasive nature of the tumor and the lack of a well-defined capsule, the first line of treatment for AAM is surgery. The diagnosis of AAM is difficult to make due to a lack of specific manifestations and specific tumor markers. In this study, we reported a case of aggressive angiomyxoma in a 2-year-old girl that rarely develops in the skull with craniocerebral compression. The patient initially had a mass on her head that attracted the attention of her family, and then she began to have episodic headaches. Surgery was performed after hospitalization, and the tumor recurred 1 year after the operation, around the originally affected skull.